A nation `living in different places': notes on the impossible work of purification in postcolonial Sri Lanka - Spencer, Jonathan (2003)
The article explores the relationship between migration and the nation-state in Sri Lanka. In particular, it investigates the shifting political and moral responses to the movement of human populations in the colonial and postcolonial periods. From at least the mid-19th century, migration was seen as something requiring active `management' by colonial officials; with the emergence of mass politics in the 1930s new rhetorics of national purity are invoked. Theoretically, the article makes two points. The first is to treat all kinds of movement - internal and external - as potentially a single phenomenon. The other is to treat the disparity between the ideal of a bounded and static national population, and the inevitably messier reality of movement, as a necessary and inevitable feature of political modernity. - Reproduced.
Keywords: Migration